ENVIRONMENTAL AND LABOR SAFETY ASPECTS OF DEGASIZATION AND PURIFICATION PROCESSES OF NON-FERROUS METAL SOLUTIONS - Parmonov Sarvar; Bekhzod Abdurafikov (Modern American Journals, 2025)
This article analyzes the environmental and occupational safety aspects of degassing of non-ferrous metal solutions and purification from non-metallic inclusions. The main risk factors arising from the use of fluxes, inert gases, and filters, the impact on the working environment, and ways to reduce them are indicated. The advantages of modern "green" fluxes, closed degassing systems, and efficient ventilation methods are highlighted, and recommendations are given for the implementation of environmentally friendly and safe technological regimes in non-ferrous metal foundries.
Keywords: Non-ferrous metals, degassing, non-metallic additives, flux, inert gas, filter, ecology, occupational safety